Counting heads vs making heads count: Impact of numeric diversity and diversity climate on psychological outcomes for faculty of color. Issue 8 (20th November 2018) - Vargas, Emily; Westmoreland, Amy Seon; Robotham, Kathrina; Lee, Fiona
Abstract : Purpose: Research on organizational diversity initiatives generally focus on either numerical diversity or racial climate. Both facets of diversity are critical, however, research has rarely examined their impact simultaneously. The paper aims to discuss these issues. Design/methodology/approach: In the current study, the authors use the context of higher education, to examine how variations in the composite of numerical diversity and racial climate predict psychological disparities between faculty of color (FOC) and White faculty. The authors test how institutions that engage in authentic diversity (i.e. institutions that are both numerically diverse and have a positive racial climate) compare to other diversity composites. Findings: Using a data set of n =37, 406 faculty members in US colleges/universities, this study found that racial disparities between FOC and White faculty for various psychological outcomes are smaller in authentic diversity institutions compared to institutions with low numeric diversity/ poor racial climate. Further, the data demonstrate that authentic diversity institutions have reduced psychological disparities compared to institutions with high numeric diversity/poor racial climate, but have similar disparities to institutions with low numeric/positive racial climate. Originality/value: These results suggest that diversity climate may be the primary driver of mitigating psychological disparities between FOC and White faculty. However, it is necessary for institutions to authentically engage in diversity – by promoting both entities – to become more effective in reducing disparities.